Method of resolving functions in the theory of conflict-controlled processes - Chikrii, A. A.; Rappoport, I. S. (Cybernetics and systems analysis, 2012)
The method of resolving functions is analyzed concerning the theory of conflict-controlled processes. Inverse Minkowski functionals play the key role. They are used to form special multivalued mappings and corresponding resolving functions, closely related to the parameters of the original conflict-controlled process. A modern technique of the theory of multivalued mappings is effectively used to substantiate game constructions and get substantial results on their basis. The problems related to the properties of special multivalued mappings and their selectors, which play a crucial role in proving the assertions, are brought into the foreground.